Selective Cytotoxic Activity of a 5-BromoIndole Carbothioamide (BTIC) Against Human Cancer Cell Lines - Fakhri, Salar A.; Abd, Abdulkareem Hameed; Abbas, Alaa H. (Journal of Pharmacology and Drug Development, 2026)
BackgroundA major limitation is the low selectivity of conventional chemotherapeutic agents, which results in severe toxicity on non-malignant tissues. Scaffolds based on indole have recently been identified as interesting new anticancer candidates but selective cytotoxicity continues to be a key target.ObjectiveThe goal of this study was to determine the cytotoxic and specific anticancer effects of a novel 5-bromo-indole-derived carbothioamide (BTIC) on several malignant and non-cancerous cell lines.MethodsAfter a 48-hour treatment, BTIC's antiproliferative effectiveness against human breast cancer (MCF-7), lung cancer (A549), & normal endothelium (HUVEC) cell lines was evaluated using the MTT assay. Data shown as dose-response curves were subjected to nonlinear regression analysis to determine IC50 values. Preferential cytotoxicity was evaluated using the selectivity index (SI).ResultsIn every cell line examined, BTIC had a cytotoxic impact; furthermore, this toxicity was concentration-dependent. This compound exhibited the most powerful activity against A549 cells (IC50 = 3.5 µg/mL), followed by MCF-7 cells IC50 (5.4 µg/mL), and significant cytotoxicity was recorded in HUVEC cells (IC50 = 10.4 µg/mL). A selective cytotoxicity on cancer cells was suggested by these reported SI values (2.97 and 1.93 for A549 and MCF-7, respectively).ConclusionBTIC was also a lead chemical with potent anticancer action against lung cancer cells in vitro, which exhibited high specificity. Therapeutic translation requires additional mechanistic and in vivo studies.